STRATEGI PEMBANGUNAN TATA KOTA DI KOTA SEMARANG - Zulfirman Siregar; Dyah Hariani; Nina Widowati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
City planning is a crucial matter in the development of a region, the increase of residents of the city in large number will narrow the available spaces, so it shall be arranged properly, this development of urban planning research is using theory of strategic management, and a SWOT analysis to identify the strengths, weaknesses, opportunities, threats, and strategic issues. The research uses descriptive qualitative. In conclusion, there are eight strategic of development in Semarang city. By using Litmus Test to evaluate this issue, there are six development strategies. The most strategic issues is carried out cooperation between the city planning department Semarang with investors and business sector.